2021
DOI: 10.1007/s40097-021-00446-1
|View full text |Cite
|
Sign up to set email alerts
|

Calcium-based nanomaterials and their interrelation with chitosan: optimization for pCRISPR delivery

Abstract: There have been numerous advancements in the early diagnosis, detection, and treatment of genetic diseases. In this regard, CRISPR technology is promising to treat some types of genetic issues. In this study, the relationship between calcium (due to its considerable physicochemical properties) and chitosan (as a natural linear polysaccharide) was investigated and optimized for pCRISPR delivery. To achieve this, different forms of calcium, such as calcium nanoparticles (CaNPs), calcium phosphate (CaP), a binary… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 124 publications
0
14
0
Order By: Relevance
“…Nanoscale platforms have been investigated for the diagnosis and treatment of various diseases. [ 1,2 ] These nanoplatforms protect the encapsulated diagnostic or therapeutic payload from degradation or premature leakage, and improve their targeting ability and biodistribution. [ 3–5 ] Although the relative success of nanocarriers has resulted in significant improvements in both efficacy and safety, compared to conventional modalities, there are still numerous challenges that hamper the clinical translation of this technology.…”
Section: Introductionmentioning
confidence: 99%
“…Nanoscale platforms have been investigated for the diagnosis and treatment of various diseases. [ 1,2 ] These nanoplatforms protect the encapsulated diagnostic or therapeutic payload from degradation or premature leakage, and improve their targeting ability and biodistribution. [ 3–5 ] Although the relative success of nanocarriers has resulted in significant improvements in both efficacy and safety, compared to conventional modalities, there are still numerous challenges that hamper the clinical translation of this technology.…”
Section: Introductionmentioning
confidence: 99%
“…The fabricated nanofibrous scaffold exhibited a high degree of biocompatibility and may be used as a tissue engineering skin substitute to expedite the healing of skin wounds 24,47 . The scaffolds were conducive to cell attachment and bridging of the fibers by cell extensions.…”
Section: Discussionmentioning
confidence: 99%
“…The results showed that after the addition of different weight ratios of chitosan to the calcium and calcium phosphate nanoparticles, the zeta potential increased considerably and led to considerable interactions with the pCRISPR. 129 Elsewhere, they demonstrated that by the addition of these PSAs to the nanostructures (nanocarriers), even highly toxic nanocarriers such as (ZnO) x (GaN) 1Àx , the relative cell viability as well as the biocompatibility and biodegradability could be increased considerably on different cell lines, leading to considerable and successful drug/ gene delivery to the targeted tissues/cells. 130 Table 4 has gathered various nanocomposite scaffolds that endorse drug/ gene delivery.…”
Section: Gene Deliverymentioning
confidence: 99%
“…3 A schematic illustrations on the preparation of nanoblends of chitosan and different calcium forms for pCRISPR delivery on the HEK-293 cell lines. 129 bacterial features (chitosan), and natural hemostasis performance (chitosan, cellulose, oxidized cellulose, carboxymethyl cellulose) are the reasons behind the use of PSAs as bloodclotting biomaterials. 154 Importantly, they must be able to be excreted from the body by natural mechanisms (such as enzymatic degradation), especially if injected into the internal parts of body (such as liver 155 ).…”
Section: Polysaccharide Nanocomposites As Hemostasis Agentsmentioning
confidence: 99%